51.4k views
1 vote
6x + 1 = 2(3x - 2) + 5 A) x = 0 B) x = 12 C) x = 1 12 D) infinitely many solutions

2 Answers

7 votes

6x + 1 = 2(3x - 2) + 5

6x + 1 = 6x - 4 + 5

6x + 1 = 6x + 1

6x = 6x

x = x

D.) Infinitely many solutions

User Tim Bartsch
by
6.3k points
2 votes

Answer:

D) infinitely many solutions

Explanation:

6x + 1 = 2(3x - 2) + 5

Distribute

6x+1 = 6x -4+5

Combine like terms

6x+1 = 6x+1

Subtract 6x from each side

6x-6x+1 = 6x-6x+1

1=1

This is always true, so x has infinite solutions

User Zishan Mohsin
by
5.8k points